Comparison of the adjuvant activity of aluminum hydroxide and calcium phosphate on the antibody response towards Bothrops asper snake venom. (January 2014) - Olmedo, Hidekel; Herrera, María; Rojas, Leonardo; Villalta, Mauren; Vargas, Mariángela; Leiguez, Elbio; Teixeira, Catarina; Estrada, Ricardo; Gutiérrez, José María; León, Guillermo; Montero, Mavis L.
Abstract The adjuvanticity of aluminum hydroxide and calcium phosphate on the antibody response in mice towards the venom of the snake Bothrops asper was studied. It was found that, in vitro, most of the venom proteins are similarly adsorbed by both mineral salts, with the exception of some basic phospholipases A2, which are better adsorbed by calcium phosphate. After injection, the adjuvants promoted a slow release of the venom, as judged by the lack of acute toxicity when lethal doses of venom were administered to mice. Leukocyte recruitment induced by the venom was enhanced when it was adsorbed on both mineral salts; however, venom adsorbed on calcium phosphate induced a higher antibody response towards all tested HPLC fractions of the venom. On the other hand, co-precipitation of venom with calcium phosphate was the best strategy for increasing: (1) the capacity of the salt to couple venom proteins in vitro; (2) the venom ability to induce leukocyte recruitment; (3) phagocytosis by macrophages; and (4) a host antibody response. These findings suggest that the chemical nature is not the only one determining factor of the adjuvant activity of mineral salts.